(untitled) (CIPEEX, 2022)
THIS WORK WAS PRESENTED DURING THE IX CULTURAL EXHIBITION OF THE DENTISTRY COURSE IN THE FORMAT OF A VIDEO-RECORDED STAGING. THE COVID-19 PANDEMIC HAS BROUGHT INSTABILITY TO MANY SECTORS OF THE WORLD ECONOMY AND THE EDUCATION SECTOR WAS NO DIFFERENT. FROM ONE DAY TO THE NEXT, THOUSANDS OF STUDENTS WHO HAD FACE-TO-FACE CLASSROOMS IN THEIR ROUTINE HAD TO ADAPT TO VIRTUAL CLASSROOMS AND THEIR REACTIONS WERE DIVERSE. SOME LOVED IT BECAUSE IT WAS AN OPPORTUNITY TO ATTEND CLASSES IN THEIR HOMETOWN, WHILE OTHERS DID NOT LIKE IT BECAUSE IN THEIR HOMES THERE WERE DOZENS OF OTHER THINGS MORE €ŒINTERESTING€ THAN ATTENDING CLASSES ONLINE. FOR TEACHERS IT WAS NO DIFFERENT, MANY HAD TO RECORD THEIR VIDEOS FOR THE FIRST TIME IN THEIR LIVES AND HAD TO ADAPT TO THIS NEW TECHNOLOGY IN RECORD TIME. THIS WORK AIMS TO PORTRAY THE ROUTINE OF ACADEMICS IN VIRTUAL CLASSROOMS FROM THE VIEW OF TEACHERS WHO TAUGHT CLASSES WHERE THE MOST INTEREST SHOULD BE. THE VIDEO IS A SATIRE THAT PORTRAYS THE MOMENT OF A LAST CALL, OFTEN, FOUR HOURS OF CLASS.